Automated machine design to shape eyes and ears of automotive crossbows - Calle Sigüencia, John Ignacio; Astudillo León, Servio Vinicio; Morocho Campos, Hernán Patricio; García Salinas, Édgar Odilón (I+ T+ C- Research, Technology and Science, 2016)
This article will develop the design of an automated machine for forming ears or eyes in automotive leaf springs. This study aims to solve the ergonomic problems currently presented in the manual process of making these auto elements. Therefore, it will analyze and design the most relevant mechanical parts, using a criterion of failure, with safety factors to ensure optimal functioning. In theory some mechanical properties of steels will be revised and regulations will be presented at the national level regarding automotive leaf springs, different processes for their preparation and international machinery used for this purpose will be exposed. In the design process the main components will be obtained for the structure of the machine, based on a mathematical analysis that will provide data necessary for sizing, the elements and the hydraulic unit generally determined in terms of standard elements will select the most efficient and easy to find in the domestic market.